Thermogravimetric analysis of anningre tannin resin - Konai, Noel; Raidandi, Danwe; Pizzi, Antonio; Girods, Pierre; Lagel, Marie Christine; Kple, Melhyas (Maderas. Ciencia y Tecnología, 2016)
Three formulations of aningre tannin resins containing in order the paraformaldehyde powder, hexamethylenetetramine and aqueous glyoxal as hardeners were developed. Their thermogravimetric analysis have shown that they begin to decompose respectively from 135°C, 145°C and 140°C. About 24%, 40% and 39 % solid residues of their initial masses exist at the end of the analysis. Thermomechanical analysis has shown that the formulation containing paraformaldehyde powder as hardener has the best rigidity and the worst contains the hexamethylenetetramine. All formulations have different thermal degradation, differences were more significant between 400 and 900°C.The decomposition of hardeners become more significant from 400°C.